(untitled) (Journal of Scientific Research, 2013)
A set is said to be a private edge dominating set, if it is an edge dominating set, for every has at least one external private neighbor in . Let and denote the minimum and maximum cardinalities, respectively, of a private edge dominating sets in a graph . In this paper we characterize connected graph for which ? q/2 and the graph for some upper bounds. The private edge domination numbers of several classes of graphs are determined. Keywords: Edge domination; Perfect domination; Private domination; Edge irredundant sets. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.12024 J. Sci. Res. 5 (2), 283-294 (2013)